ASSESSING THE EFFECT OF ORGANISATIONAL CHANGE ON PERFORMANCE (SIERRA LEONE COMMERCIAL BANK) (SLCB) - Musa, Vinord; Kamara, Duramany (Technium Education and Humanities, 2024)
This study aimed to evaluate the impact of organizational change on performance in the banking industry, specifically in Sierra Leone Commercial Bank (SLCB). The bank has been undergoing significant organizational changes due to the Covid-19 pandemic, competition, continuous value addition, and emphasis on customer satisfaction and profitability. The study found that the bank's current trends reflect a sense of urgency to revitalize its system to meet customer needs effectively. Employees are now expected to adapt their thinking and practices to meet the changing needs and expectations of customers, especially in the face of increased competition. The study aimed to understand employees' understandings of change management initiatives, their effectiveness, and their impact on the bank as a whole. Data was gathered from 50 randomly selected employees using questionnaires and interviews, and the data was processed using the Statistical Package for Social Sciences (SPSS). The findings revealed a significant positive relationship between organizational change and performance, with change having a positive relationship with employee performance, leading to improved organizational performance. The study also found that change management programs are effective. Employees' understandings of change and management are more apparent during times of change, helping them accept, facilitate, and support the change, making it lasting and improving employee and organizational performance.